DIGITAL MARKETING OF CITRA MOBIL INDO IN USED CAR SALES - Adam Alifandra Khalifah; Nur Maghfirah Aesthetika (International Journal of Economic Integration and Regional Competitiveness, 2024)
This study explores the strategic significance of digital marketing in influencing consumer behavior on social media, particularly within the used car trading sector exemplified by Citra Mobil Indo. General Background: As digital platforms increasingly dominate marketing landscapes, businesses are tasked with adapting to new consumer engagement strategies. Specific Background: Citra Mobil Indo employs a targeted digital marketing approach, utilizing social media marketplaces to promote and sell used cars effectively. Knowledge Gap: Despite the proliferation of digital marketing in the automotive sector, there remains a lack of comprehensive analysis regarding its efficacy and the specific challenges encountered in these online environments. Aims: This research aims to evaluate the effectiveness of Citra Mobil Indo's digital marketing strategies and identify the obstacles faced in the sales process. Results: Utilizing a qualitative descriptive method, findings reveal that Citra Mobil Indo's sales efforts on Facebook Marketplace are both relevant and aligned with ongoing market digitization trends, with 70% of sales conducted through digital channels from a sample of 10 transactions. Novelty: This study offers new insights into the application of digital marketing strategies in the used car industry, emphasizing the critical role of social media in shaping consumer interactions. Implications: The findings highlight the necessity for enhanced consumer protection measures against fraud within social media transactions, providing actionable recommendations for businesses to strengthen their digital marketing frameworks and safeguard against potential risks.